Forest Protection against Illegal Logging (In the Forest Area of Perhutani Public Company Mantingan Forest Management Unit, Rembang Regency, Central Java) - Amar Lukman Hakim; Nuria Siswi Enggarani (Proceeding International Conference Restructuring and Transforming Law, 2024)
This research is a study of forest protection against illegal logging in the Forest area of Perhutani Public Company Mantingan Forest Management Unit, Rembang. The method used in this research is qualitative research method. In this study researchers used a sociological juridical approach, the role of the government in forest protection against illegal logging in the Forest area of the Public Company Perhutani Mantingan Forest Management Unit, namely by conducting preemptive activities such as communicating and raising awareness to the public of the impact of illegal logging and providing socialization related to penalties for illegal loggers. The government also carries out preventive activities such as prevention activities against illegal logging by forming teams to protect forest areas. Meanwhile, the policy taken by the government of the Forest area of the Perhutani Public Company Mantingan Forest Management Unit of Rembang is repressive activities where the government will take action against perpetrators of illegal logging. Based on this, it can be concluded that the community and government have an important role in maintaining and preventing illegal logging activities that can damage the forest and will pose a serious threat to the flora and fauna in the forest area.